Ongoing Challenges of Extubation of COVID-Pneumonic Patient in Multi-Organ Failure: a Case Report - Aziz, Md Zulfiker Riad Ibn; Arif, Md Masum Hossain; Mamun, Abdullah Al; Noor, A K M Abdun; Jakaria, A K M; Chowdhury, Mahfuz Ahmed; Hudaibi, Khondoker Hasan Al; Noor, Md Mahbub; Islam, Md Sadiqul (Pulse, 2024)
In this report, a case of a patient with COVID-19 pneumonia is presented who developed multi-organ failure and required mechanical ventilation. Despite multiple attempts at extubation, the patient remained intubated for an extended period due to respiratory failure. The challenges encountered during the process of extubation are discussed and the strategies employed to overcome them. This case highlights the importance of careful decision and management in patients with COVID-19 pneumonia for extubation who develop multi-organ failure. Pulse Vol.15, 2023 P: 45-50